2021
DOI: 10.5040/9781350104716
|View full text |Cite
|
Sign up to set email alerts
|

Fashion and Cultural Studies

Abstract: Bridging theory and practice, this accessible text considers fashion from both cultural studies and fashion studies perspectives, and addresses the growing interaction between the two fields. Kaiser and Green use a wide range of cross-cultural case studies to explore how race, ethnicity, class, gender and other identities intersect and are produced through embodied fashion. Drawing on intersectionality in feminist theory and cultural studies, Fashion and Cultural Studies is essential reading for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 0 publications
1
93
0
6
Order By: Relevance
“…Researchers have found that Black people have historically used dress as a way to express Black identity and reject abuses of power, racism, and discrimination in their many forms (Delgado & Stefancic, 2017;Ford, 2015;Tyler, 2008). An early example of Black and activist identity being expressed through dress by Black men is the zoot suit, which became an expression of rebellion against hegemonic norms during the 1940s (Kaiser, 2012;Tyler, 2008). Our research participants confirmed that the act of rebellion through dress is still happening today, specifically in relation to the BLM era, and they shared they often use garments such as slogan T-shirts to express their Black and activist identities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers have found that Black people have historically used dress as a way to express Black identity and reject abuses of power, racism, and discrimination in their many forms (Delgado & Stefancic, 2017;Ford, 2015;Tyler, 2008). An early example of Black and activist identity being expressed through dress by Black men is the zoot suit, which became an expression of rebellion against hegemonic norms during the 1940s (Kaiser, 2012;Tyler, 2008). Our research participants confirmed that the act of rebellion through dress is still happening today, specifically in relation to the BLM era, and they shared they often use garments such as slogan T-shirts to express their Black and activist identities.…”
Section: Discussionmentioning
confidence: 99%
“…Our different identities are often reflected through dress and continually negotiated on an everyday basis (Kaiser, 2012). Throughout history, Black people have purposely performed their Blackness and activist identities through their dress such as wearing denim, African-inspired garments, bright colors, bold jewelry, or political slogans (Ford, 2015;O'Neal, 1998).…”
Section: Brief History Of Negotiations Of Black and Activist Identity...mentioning
confidence: 99%
See 3 more Smart Citations